Biochemical Mechanism of Insecticide Resistance in Malaria Vector, Anopheles gambiae s.l in Nigeria - Mustapha Ahmed YUSUF; Hassan VATANDOOST; Mohammad Ali OSHAGHI; Ahmad Ali HANAFI-BOJD; Abdulsalam Yayo MANU; Ahmadali ENAYATI; Abduljalal ADO; Alhassan Sharrif ABDULLAHI; Rabiu Ibrahim JALO; Abubakar FIRDAUSI (Tehran University of Medical Sciences, 2020)
Background: Malaria is a parasitic vector-borne disease endemic in the tropical and subtropical countries of the world. The aim of this study was to investigate the current activities of the detoxification enzymes in resistant and susceptible Anopheles gambiae s.l. in northern Nigeria. Methods: Anopheles larvae were collected from northeast and northwestern Nigeria between Aug and Nov 2018. Biochemical analyses was carried out on the mosquitoes exposed to various insecticides (deltamethrin, DDT, bendiocarb, malathion) to measure and compare the enzymatic activities of the major detoxification enzymes (P450, GSTs, Esterase). Results: High levels of resistance was observed; DDT 37%-53% (95%, CI: 29-61), bendiocarb 44%-55% (CI: 39-60) and deltamethrin 74%-82% (CI: 70-86). However, these mosquitoes were found to be susceptible to malathion 99%-100% (CI: 98-100). The P450 and GSTs enzymes were found to be elevated in the resistant mosquitoes exposed to deltamethrin (1.0240±0.1902); (1.3088±1.2478), DDT (1.7703±1.4528); (1.7462±0.9418) and bendiocarb (1.1814±0.0918); (1.4479±1.0083) compared to the Kisumu strain (0.764±0.4226); (0.6508±0.6542), (0.3875±0.3482); (0.4072±0.4916) and (0.6672±0.3949); (0.7126±0.7259) at P<0.05. Similarly, the resistant mosquitoes expressed increased activity to esterase (0.7606±1.1477), (0.3269±1.1957) and (2.8203±0.6488) compared to their susceptible counterpart (0.6841±0.7597), (0.7032±0.5380) and (0.6398±0.4159) at P<0.05. The enzyme ratio was found to be: P450 (1.341, 4.568 and 1.77); GSTs (2.011, 4.288 and 2.031); Esterases (1.111, 0.469 and 4.408). One way Anova and single sample t-test were also conducted to determine the effect of the enzymes on the resistant and susceptible strains. Conclusion: High level of insecticide resistance was observed with significant elevation of detoxification enzymes activities in the resistant mosquitoes.